2015
DOI: 10.1371/journal.pone.0125749
|View full text |Cite
|
Sign up to set email alerts
|

Criteria-Based Audit of Quality of Care to Women with Severe Pre-Eclampsia and Eclampsia in a Referral Hospital in Accra, Ghana

Abstract: ObjectivesSevere pre-eclampsia and eclampsia are one of the major causes of maternal mortality globally. Reducing maternal morbidity and mortality demands optimizing quality of care. Criteria-based audits are a tool to define, assess and improve quality of care. The aim of this study was to determine applicability of a criteria-based audit to assess quality of care delivered to women with severe hypertensive disorders in pregnancy, and to assess adherence to protocols and quality of care provided at a regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Although evidence suggests that severe hypertension is a similarly important contributor to maternal mortality in sHDP, antihypertensives are not included in the signal functions, and this omission might have contributed to more than half of the women with sHDP at baseline not receiving antihypertensive treatment. A similar mismatch in pre‐eclampsia/eclampsia treatment was reported in Ghana, where health providers described how clinical guidelines were adhered to more closely if they were given more attention and if local adjustments were made . A second version of the brief and simple PartoMa pocket guide was launched in 2018, with the focal point broadened further by including additional essential intrapartum and postpartum care, and PartoMa seminars have now been conducted for nearly 4 years…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Although evidence suggests that severe hypertension is a similarly important contributor to maternal mortality in sHDP, antihypertensives are not included in the signal functions, and this omission might have contributed to more than half of the women with sHDP at baseline not receiving antihypertensive treatment. A similar mismatch in pre‐eclampsia/eclampsia treatment was reported in Ghana, where health providers described how clinical guidelines were adhered to more closely if they were given more attention and if local adjustments were made . A second version of the brief and simple PartoMa pocket guide was launched in 2018, with the focal point broadened further by including additional essential intrapartum and postpartum care, and PartoMa seminars have now been conducted for nearly 4 years…”
Section: Discussionmentioning
confidence: 77%
“…A previous facility‐based survey in low‐ and middle‐income countries found that the likelihood of maternal near‐miss was eightfold and perinatal death threefold higher in a group of women with pre‐eclampsia than in a reference group without HDP . Although most cases are preventable, undiagnosed or suboptimally treated HDP is repeatedly reported in sub‐Saharan Africa . This violates human rights and is a key priority for safe motherhood …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations